URGENSI PENETAPAN KRITERIA FAKIR MISKIN BAGI PENYALURAN ZAKAT DI INDONESIA (ZISWAF: Jurnal Zakat dan Wakaf, 2017)
Poverty has many definitions, parameters, and standards. From the viewpoint of Islam, many theologians define and measure poverty by various terms and sizes. The difference among theologians’ opinion is caused by poverty terms contained in the Qur’an and Hadits. “Fakir” and “poor” have many meanings. It allows a wide interpretation of the verse and word from theologians. It is also seen from the regulation point in Indonesia, there are many definitions, standards and parameters of poverty. The difference of point of view on determination of poverty criteria and regulations according to Islam in Indonesia shows that the ways of ijtihad by theologians and the government elements is very open. The absence of standard stipulation held, encouraging the writer to conduct a comparative research in this paper; through literacy research. Syafi’i sect does not specify a quantitative standard for poverty. Poverty is only categorized on requirement. As long as people are not able to cover 50% of their basic needs, they are called as fakir. If people are only able to cover close to 70% of their basic needs then they are categorized as poor. Meanwhile, according to Hanafi sect, the qualitative standards turned to the Syafi’i sect. Poor conditions are more severe than the fakir. Besides,the quantitative standard of poverty is one nisab of zakat or the equivalent of 85 grams of gold. On the other hand, BPS and BKKBN formulate the concept and standard of poverty by economic concepts. Poverty is conceptualized as the inability of someone to meet basic consumption needs of the formulation adapted to local conditions respectively.